The study of radiation contamination in roodepoort gold mine tailings using HPGe gamma spectroscopy - Mvelase, Mashinga J.; Ntshangase, Sifiso S.; Majola, Siyabonga N. T.; Kheswa, Bonginkosi V.; Masiteng, Paulus L.; Maleka, Peane P. (Frontiers in Physics, 2026)
In this study, a coaxial HPGe high-resolution γ-detector was used to measure the γ-signals in soil samples collected from the Roodepoort Gold Tailings. There have been complaints about dust from the gold tailings, and the study aims to determine the level of contamination. The activity concentration of 238U ranged from 132.88 ± 4.68 to 1,421.46 ± 13.38, with a mean of 464.96 ± 2.08 Bq/kg. The activity concentration of 226Ra ranged from 130.19 ± 4.48 to 1,359.27 ± 13.83, with a mean of 425.28 ± 8.02 Bq/kg. The range of 232Th was from 5.27 ± 0.67 to 19.37 ± 1.98, with a mean of 11.20 ± 1.03 Bq/kg, and 40K activity ranged from 65.23 ± 15.29 to 264.11 ± 25.66, with a mean of 127.50 ± 21.85 Bq/kg. The findings showed that 238U and 226Ra activities exceeded the global average of 35 Bq/kg, while 232Th and 40K were below their respective limits. The radiological hazard indices exceeded recommended limits, making the tailings soil completely unsuitable for use as building materials, as this may have deleterious health effects on residents in the future.